MEMPERSOALKAN ETIKA DAN MORAL PEGAWAI NEGERI SIPIL PASCA ORDE BARU - John Fresly Hutahayan (Jurnal Manajemen Kepegawaian, 2008)
This paper pointed out that ethic and moral is a key factor to speed up bureaucratic reform in Indonesia. As a matter of fact, public service in Indonesia is hamper by systemic problems involving all actors in the system from high level officer to the low rank officer. Although regulation regarding ethic and moral of the government official sufficient enough to promote certain high standard code of conduct, the bureaucratic behavior is far from ideal. Indeed, bureaucratic behavior is a mixed of individual characteristic and bureaucratic characteristic. It is impossible to change bureaucratic behaviour without give attention to these two aspects. To solve this problem, leadership in Civil Servant Institution is crucial as a breakthrough to cut the vicious circle of buraucracy.Keywords: Bureaucratic Behaviour, Government Official, Ethic and Moral.